2015
DOI: 10.1038/pr.2015.93
|View full text |Cite
|
Sign up to set email alerts
|

Do children with congenital hypothyroidism exhibit abnormal cortical morphology?

Abstract: Background: Given thyroid hormone (TH)'s essential role in multiple aspects of early brain development, children with congenital hypothyroidism (CH) detected and treated early may still display subtle cognitive and behavioral impairments as well as brain abnormalities. However, effects on their cortical development are not yet known. We used an automated neuroimaging technique to determine if these children differ in cortical thickness (CT) from typically developing controls (TDC) and if the regions showing CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 43 publications
2
27
1
Order By: Relevance
“…Importantly, the visual system is a known target for TH regulation during development (Berbel et al, 2010;Martinez-Galan, Escobar del Rey, Morreale de Escobar, Santacana, & RuizMarcos, 2004). As recently demonstrated by Clairman et al (2015), children who are deficient in TH during pregnancy, despite receiving early and continuous treatment after birth, experience aberrant neural development involving both cortical thinning and cortical thickening, including in regions belonging to both visual streams.…”
Section: Discussion Of Study 2 Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Importantly, the visual system is a known target for TH regulation during development (Berbel et al, 2010;Martinez-Galan, Escobar del Rey, Morreale de Escobar, Santacana, & RuizMarcos, 2004). As recently demonstrated by Clairman et al (2015), children who are deficient in TH during pregnancy, despite receiving early and continuous treatment after birth, experience aberrant neural development involving both cortical thinning and cortical thickening, including in regions belonging to both visual streams.…”
Section: Discussion Of Study 2 Resultsmentioning
confidence: 98%
“…Nevertheless, because of their brief period of TH deficiency before treatment is received and takes effect, they still may show mild cognitive deficits, the nature and severity of which reflect the specific timing of their TH deficiency (Rovet, 2005). Structural neuroimaging studies of children with CH report that multiple brain regions show abnormal cortical thickness, including thinning of the superior parietal gyrus and precuneus, which belong to the dorsal stream, and inferior temporal gyrus belonging to the ventral visual stream (Clairman, Skocic, Lischinsky, & Rovet, 2015). Previous behavioral studies by our group and others suggest that visuospatial deficits in CH may be specific to the dorsal stream (Blasi et al, 2009;Leneman, Buchanan, & Rovet, 2001;Mirabella et al, 2005).…”
mentioning
confidence: 99%
“…It is relevant to note we recently reported that children with CH, who underwent a brief circumscribed period of TH insufficiency that occurred somewhat later and extended longer than in HYPO, also showed that cortical thinning and thickening relative to controls and effects reflected the severity of their hypothyroidism ( 45 ). Both CH and HYPO conditions showed thinning of the right precuneus and thickening in right occipital regions, while left precentral gyrus and right cuneus and postcentral gyrus thickening were correlated with late gestational or perinatal TH elevations in both populations.…”
Section: Discussionmentioning
confidence: 97%
“…Image analysis was performed on a Linux Fedora operating system using FreeSurfer Image Analysis Suite version 4.4 ( 53 ). When this study originally began, this version was the most current and used in other research in our lab ( 45 ). FreeSurfer consists of a series of automated algorithms that reproduce the brain’s inner and outer surfaces and measure distances between these surfaces on a point-to-point basis for the entire cortical mantle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation